INCREASING PURCHASE ACTION RATIO (PAR) THROUGH AN EFFECTIVE INSTAGRAM CAMPAIGN IN SELECTED ASIA COUNTRIES: A CASE STUDY OF GLOBAL MILLENNIAL MUN - Febrian Ahmad (CV. RADJA PUBLIKA, 2025)
The rapid development of digital marketing has transformed the way organizations engage with their audiences, particularly through the use of social media as a primary marketing communication channel. In the context of international marketing, campaign effectiveness is no longer assessed solely by exposure or engagement metrics, but by the ability to convert awareness into concrete actions. One key indicator of this effectiveness is the Purchase Action Ratio (PAR), which reflects the proportion of exposed audiences who proceed to take actual action. Global Millennial Model United Nations (GM MUN), an international education-based organization, faces a critical challenge in which high levels of international brand awareness generated through Instagram are not accompanied by proportional international participation. This study aims to analyze the factors contributing to the low conversion of international audience awareness into registration actions at GM MUN and to evaluate the effectiveness of its international marketing strategy implemented through Instagram campaigns. The research adopts a mixed methods approach with a primary qualitative orientation, enabling both the identification of performance patterns and an in-depth understanding of audience perceptions and decision-making processes. Data were collected through semi-structured interviews with internal and external stakeholders, observation of GM MUN’s Instagram activities, and analysis of supporting campaign and registration documents. The analysis is guided by the integration of the Marketing 5.0 framework, marketing communication, social media marketing, and the 5A customer journey model (Aware, Appeal, Ask, Act, Advocate). The findings indicate that GM MUN has successfully generated strong international awareness and initial interest, particularly at the Aware and Appeal stages. However, the marketing strategy remains predominantly awareness-driven and insufficiently optimized to encourage progression toward the Ask and Act stages. Key conversion barriers include unclear international segmentation that relies heavily on geographic criteria, weak institutional credibility signaling, limited persuasive messaging and structured calls to action, and suboptimal management of later stages of the customer journey. This study concludes that GM MUN’s low PAR is not a result of insufficient visibility, but rather a misalignment between awareness-building efforts and conversion-oriented strategies. Accordingly, the study recommends a strategic shift toward conversion-focused international marketing through role-based segmentation refinement, strengthened institutional credibility, improved persuasive communication, and optimized international customer journey management. The findings are expected to provide practical insights for international event and education organizers, while contributing to academic discussions on digital marketing effectiveness in cross-border contexts.